Spider composition at Hulu Langat Recreational Forest Parks, Selangor, Malaysia - Sarkowi, Fateen Noorasyiqin; Hong, Lau Wei (International Organization of Scientific Research, 2020)
A study was done to investigate the spider composition at Sungai Gabai and Sungai Tekala Recreational Forest Parks located at Hulu Langat, Selangor, Malaysia. The sampling was done along the riparian area of the river stream. A total of 26 individuals of spiders were collected from both recreational forest park and comprised of 8 families: Tetragnathidae, Oxyopidae, Araneidae, Salticidae, Sparassidae, Nephilidae, Theridiidae and Lycosidae. There were 142 individuals and 14 species collected from the Sungai Gabai Recreational Forrst Park, and 119 individuals and 14 species collected from Sungai Tekala Recreational Forest Park. Tetragnathidae spiders have dominated both Sungai Gabai and Sungai Tekala Recreational Forest Park with 81% and 61% of total relative abundance, respectively. Shannon’s index indicates that Sungai Tekala Recreational Forest Park (1.164) has higher diversity index compared to Sungai Gabai Recreational Forest Park (0.767). Simpson’s index has revealed that Sungai Gabai Recreational Forest Park has more diverse spider family than Sungai Gabai Recreational Forest Park which was dominated by only one spider family, namely Tetragnathidae.